(untitled) - Baach, Christel (Thành phố Hồ Chí Minh, 1992)
The Speak To Me learning system is one of the fastest, easiest, and surest ways to learn English. All you need is a VCR, a television, and the desire to learn English. Learn quickly. You will find that you understand the basics of English almost immediately. Every day you will add new words and phrases to your vocabulary. Speak To Me works for everyone! Beginners will be able to communicate effectively right away. Intermediate to advanced can use the video to improving vocabulary and refining their accents.
Keywords: English language; Study and teaching